2014
DOI: 10.1155/2014/252171
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mushroom Beta‐Glucans from Solid Culture of Ganoderma lucidum on Inhibition of the Primary Tumor Metastasis

Abstract: This study evaluates the effect of mushroom beta-glucans (MBGS) derived from solid culture of Ganoderma lucidum on tumor inhibition by examining size of the primary tumor and rate of metastasis in Lewis lung carcinoma (LLC) bearing mice (C57BL/6), given oral administration of MBGS with radiation therapy. A previous result showed that MBGS enhances NK cell-mediated cytotoxicity in mice without LLC bearing in advance. Furthermore, applications of MBGS in conjunction with radiation therapy were effective in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…When MBGS is administered in conjugation with radiation therapy it serves as a protective factor for the hair loss and wounds due to the overgrowth of primary tumor in LLC bearing mice. It is also effective in controlling tumor growth and rate of metastasis [41].…”
Section: Effect Of G Lucidum On Lewis Lung Carcinoma Bearing Micementioning
confidence: 99%
“…When MBGS is administered in conjugation with radiation therapy it serves as a protective factor for the hair loss and wounds due to the overgrowth of primary tumor in LLC bearing mice. It is also effective in controlling tumor growth and rate of metastasis [41].…”
Section: Effect Of G Lucidum On Lewis Lung Carcinoma Bearing Micementioning
confidence: 99%
“…A previous results showed that beta-glucans enhanced NK cell-mediated cytotoxicity in mice without lung carcinoma bearing in advance. Furthermore, applications of beta-glucans in conjuction with radiation therapy were effective in controlling tumor growth, and rate of metastasis, life threatening and can potentially serve as protective factor for wounds and hair loss that resulted from overgrowth of primary tumor in Lewis lung carcinoma bearing mice [5].…”
Section: The Effects Of Beta-glucans In Vitro and In Animal Studiesmentioning
confidence: 99%
“…Ganoderma lucidum, also known as lingzhi, mannentake, immortality mushroom, and red reishi mushroom, is the oldest known mushroom species used in Chinese and Japanese medicine, i.e. for more than 2000 years (1). It is believed that herbal drugs produced from this mushroom can cure diseases such as cardiovascular diseases, diabetes, renal failure, and cancers (1).…”
Section: Introductionmentioning
confidence: 99%
“…for more than 2000 years (1). It is believed that herbal drugs produced from this mushroom can cure diseases such as cardiovascular diseases, diabetes, renal failure, and cancers (1). In our presentation, we aim to discuss a case with acute hepatorenal failure associated with the use of reishi mushroom.…”
Section: Introductionmentioning
confidence: 99%